2020
DOI: 10.1016/j.vaccine.2020.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic response on uptake of routine immunizations in Sindh, Pakistan: An analysis of provincial electronic immunization registry data

Abstract: Highlights One out of two children missed routine immunizations during COVID-19 lockdown in Sindh. COVID-19 lockdown disproportionately affected coverage rates across the districts. Drop in the number of immunizations was higher in rural areas followed by urban slums. Expanding pool of un-immunized children is bringing down herd immunity and raising the risk of vaccine-preventable disease outbreaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
239
3
13

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(258 citation statements)
references
References 21 publications
3
239
3
13
Order By: Relevance
“…Our model is inline with very recent reports on the decline in pediatric vaccination, that show a substantial impact of the pandemic on routine vaccination in the United States and across the world and concerns around decrease in vaccination worldwide [9] , [10] , [11] . Our results add to the literature by translating possible declines in vaccination to a common benchmark, recognized by infectious disease modelers and policy makers alike.…”
Section: Discussionsupporting
confidence: 67%
“…Our model is inline with very recent reports on the decline in pediatric vaccination, that show a substantial impact of the pandemic on routine vaccination in the United States and across the world and concerns around decrease in vaccination worldwide [9] , [10] , [11] . Our results add to the literature by translating possible declines in vaccination to a common benchmark, recognized by infectious disease modelers and policy makers alike.…”
Section: Discussionsupporting
confidence: 67%
“…With increased poverty and undernutrition, TB cases may surge among these disadvantaged communities. Furthermore, as regular services continue to be disrupted, routine TB immunization programs have been affected, such as in Pakistan, where an over 40% decline in BCG vaccinations has been reported [63].…”
Section: Resultsmentioning
confidence: 99%
“…Much of the literature on the impact of the pandemic on vaccination coverage consists of modeling exercises with hypothetical data, as few studies are available from low- and middle-income countries that included actual measurements of the shortfall. 5 A study in Afghanistan showed that due to Covid-19 spread, polio vaccine coverage was reduced and reported cases increased. 6 At the main university hospital in Saudi Arabia, a retrospective cohort from 2017 to 2020 found that coverage with all childhood immunizations, except for vaccines administered soon after birth were around 20% to 50% lower in 2020 compared with 2017 to 2019.…”
Section: Introductionmentioning
confidence: 99%